Bahasa Inggris - Resti CItra Dewi; Isa Hidayati; Supriadi (Institut Agama Islam Negeri Madura, 2024)
This research is classroom action research (PTK). This research aims to improve English vocabulary mastery through video media at Bina Jaya Kindergarten to make it even better. The subjects of this research were 13 Bina Jaya Kindergarten children consisting of 8 boys and 5 girls. This research was conducted at Bina Jaya Kindergarten Jl.protokol, Sawit Seberang, Langkat, North Sumatra. The data collection technique is carried out directly and is adapted to the observation format. The instrument used is observation of children in the process of learning to introduce English vocabulary through the use of Youtube video media and documentation. Based on the research results, it shows that with action, there is an increase in the pre-cycle percentage of student's learning achievements reaching 30.76% with the MB criteria. The percentage of children's learning achievement increased in cycle 1 when the percentage reached 69.71%. This percentage increased by 38.95% compared to the percentage in the pre-cycle. An increase also occurred in cycle 2 where the percentage of children's achievements reached 79.81%, an increase of 10.1% compared to the percentage in cycle 1. From the research results, it can be concluded that Youtube video media can improve the ability to master English vocabulary by listening to English vocabulary. , pronounce English vocabulary, mention English vocabulary and write English vocabulary.